Improving the prediction of long‐term readmission and mortality using a novel biomarker panel. Issue 11 (2nd September 2021) - Brown, Jeremiah R.; M. Parker, Devin; Stabler, Meagan E.; Jacobs, Marshall L.; Jacobs, Jeffrey P.; Everett, Allen D.; Lobdell, Kevin W.; Wyler von Ballmoos, Moritz C.; Thiessen‐Philbrook, Heather; Parikh, Chirag; Mackenzie, Todd; DiScipio, Anthony; et al.
Abstract: Objective: Several short‐term readmission and mortality prediction models have been developed using clinical risk factors or biomarkers among patients undergoing coronary artery bypass graft (CABG) surgery. The use of biomarkers for long‐term prediction of readmission and mortality is less well understood. Given the established association of cardiac biomarkers with short‐term adverse outcomes, we hypothesized that 5‐year prediction of readmission or mortality may be significantly improved using cardiac biomarkers. Materials and Methods: Plasma biomarkers from 1149 patients discharged alive after isolated CABG surgery from eight medical centers were measured in a cohort from the Northern New England Cardiovascular Disease Study Group between 2004 and 2007. We assessed the added predictive value of a biomarker panel with a clinical model against the clinical model alone and compared the model discrimination using the area under the receiver operating characteristic (AUROC) curves. Results: In our cohort, 461 (40%) patients were readmitted or died within 5 years. Long‐term outcomes were predicted by applying the STS ASCERT clinical model with an AUROC of 0.69. The biomarker panel with the clinical model resulted in a significantly improved AUROC of 0.74 ( p value <.0001). Across 5 years, the hazard ratio for patients in the second to fifth quintile predicted probabilities from the biomarker augmented STS ASCERT model ranged from 2.2 to 7.9 ( p values <.001). Conclusions: We report that a panel of biomarkers significantly improved prediction of long‐term readmission or mortality risk following CABG surgery. Our findings suggest biomarkers help clinical care teams better assess the long‐term risk of readmission or mortality.